ChemInform Abstract: Ti/Ni‐Mediated Inter‐ and Intramolecular Conjugate Addition of Aryl and Alkenyl Halides and Triflates. Issue 31 (5th August 2014) - Marquez, Irene R.; Miguel, Delia; Millan, Alba; Marcos, M. Luisa; Alvarez de Cienfuegos, Luis; Campana, Araceli G.; Cuerva, Juan M.
Abstract A new, direct inter‐ and intramolecular coupling of α, β‐unsaturated carbonyl compounds with aryl and alkenyl halides and triflates is developed.